Synthesis of CTA and DNAN Using Flow Chemistry. Issue 10 (12th September 2022) - Mittal, Ankit Kumar; Prakash, Gaurav; Pathak, Pramod; Maiti, Debabrata
Abstract: This paper describes a flow chemistry approach for synthesising two high‐energy molecules, cyanuric triazide (CTA) and 2, 4‐dinitroanisole (DNAN), and scaling them up to multi‐gram scale using an automated flow reactor system. The flow chemistry approach offers high degree of safety and easy to scale compared to conventional syntheses. The development of two processes: a. CTA via azidation of cyanuric chloride; b. DNAN via methoxylation of 2, 4‐dinitrichlorobenzene (2, 4‐DNCB) on an automated commercially available flow reactor system is described. High yield (>95%) was achieved in both the processes. Very short reaction times (30 seconds) were applied. The process parameters were optimized using the automated flow chemistry system. The optimized process was scaled to multi gram scale (>30 g/hr). The method can be considered fit for the safe production of CTA and DNAN at multi gram scale in laboratory. Abstract : Highly scalable synthesis of CTA (via azidation of cyanuric chloride) and DNAN (via methoxylation of 2, 4‐DNCB) using a flow chemistry methodology was developed.